2017
DOI: 10.1007/s11325-017-1578-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral appliance treatment outcome can be predicted by continuous positive airway pressure in moderate to severe obstructive sleep apnea

Abstract: BackgroundStudies show that the therapeutic CPAP pressure is associated with oral appliance (OA) treatment outcome in obstructive sleep apnea (OSA) patients. However, these studies included either CPAP adherent patients using fixed pressure devices, or partly CPAP non-adherent patients using fixed pressure or auto-adjusting (auto-CPAP) devices. In many countries, auto-CPAP is predominately used, and only those non-adherent to therapy need a change to OA. Therefore, studies examining the relationship between CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Our observed findings related to HGNS are in accordance with studies investigating the predictive value of therapeutic PAP level for oral appliance therapy (OAT) outcomes. [13][14][15] Oral appliances are orthodontic retainers that advance the mandible to maintain a patent airway. 24 In the first study by Tsuiki et al, a cohort of 35 CPAP-adherent Japanese men (mean age 55 years, BMI 26 kg/m 2 , baseline AHI 37 events/h) were asked to stop using CPAP prior to being fitted with an oral appliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observed findings related to HGNS are in accordance with studies investigating the predictive value of therapeutic PAP level for oral appliance therapy (OAT) outcomes. [13][14][15] Oral appliances are orthodontic retainers that advance the mandible to maintain a patent airway. 24 In the first study by Tsuiki et al, a cohort of 35 CPAP-adherent Japanese men (mean age 55 years, BMI 26 kg/m 2 , baseline AHI 37 events/h) were asked to stop using CPAP prior to being fitted with an oral appliance.…”
Section: Discussionmentioning
confidence: 99%
“…12 This finding is interesting in the setting of three independent studies, which found that patients with low therapeutic PAP levels were more likely to succeed with oral appliances for OSA. [13][14][15] In this study, we sought to determine whether therapeutic PAP level predicts outcomes following HGNS for OSA. Our primary aim was to determine whether there is a difference in reduction of AHI or 4% oxygen desaturation index (ODI4) between patients with low and high PAP levels.…”
Section: Introductionmentioning
confidence: 99%
“…Both therapeutic PAP level and airway opening response to mandibular advancement (MA) on DISE have been shown to predict successful treatment of OSA with a MAD. 13,14 Recently, our group has shown that akin to MAD patients, HGNS patients with low therapeutic PAP levels are more likely to succeed compared to patients with higher pressure requirements. 15 At present, it is unclear if response to MA during DISE can similarly aid in the selection of HGNS candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Mandibular advancement devices (MAD) represent a leading nonsurgical alternative to positive airway pressure (PAP) therapy. Both therapeutic PAP level and airway opening response to mandibular advancement (MA) on DISE have been shown to predict successful treatment of OSA with a MAD 13–14 . Recently, our group has shown that akin to MAD patients, HGNS patients with low therapeutic PAP levels are more likely to succeed compared to patients with higher pressure requirements 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A study assessed whether CPAP pressures predicted OAT outcomes in patients that failed auto-CPAP therapy. 295 According to the authors, research has demonstrated that therapeutic CPAP pressure is associated with OAT outcomes in patients with OSA. These studies included either CPAP-adherent patients using fixed pressures or partly CPAP nonadherent individuals using fixed pressures or auto-adjusting (a-PAP) devices.…”
Section: Oral Appliance Therapymentioning
confidence: 99%